Region-specific differentiation of neural tube-derived neuronal restricted progenitor cells after heterotopic transplantation - Yang, Hui (The National Academy of Sciences, 2000)
Spinal cord neuronal restricted progenitor (NRP) cells, when transplanted into the neonatal anterior forebrain subventricular zone, migrate to distinct regions throughout the forebrain including the olfactory bulb, frontal cortex, and occipital cortex but not to the hippocampus. Their migration pattern and differentiation potential is distinct from anterior forebrain subventricular zone NRPs. Irrespective of their final destination, NRP cells do not differentiate into glia. Rather they synthesize neurotransmitters, acquire region-specific phenotypes, and receive synapses from host neurons after transplantation. Spinal cord NRPs express choline acetyl transferase even in regions where host neurons do not express this marker. The restricted distribution of transplanted spinal cord NRP cells and their acquisition of varied region-specific phenotypes suggest that their ultimate fate and phenotype is dictated by a combination of intrinsic properties and extrinsic cues from the host.